2011
DOI: 10.2174/157340111797264804
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Milk Lipids

Abstract: 8Current information about the nutritional composition of milk fat is required for the consumer and therefore 9 essential for the successful development of dairy industries as well as marketing their products. The progress 10 in the knowledge concerning some milk fat components that possess biological properties and health benefits 11 beyond their nutritional significance, have a growing interest in the dairy industry to design and formulate 12 products that incorporate specific bioactive components derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…The major differences in the composition of milk and yogurts made from ewe’s and cow’s milk lie in the higher protein and fat content of the former, as well as higher amounts of vitamins, calcium, and phosphorus [15,65]. As indicated previously, ewe’s milk is richer in fat and SFA than cow’s milk, and a number of studies have shown that it offers a healthier nutritional profile than that of the cow, especially because of its higher content in short-chain FA (SCFA) from butyric to caproic acid, C4 to C10 (SCFA, see Table 2), associated with health benefits [66,67]. Besides SCFA, there are other beneficial lipids, such as the unsaturated FA, including MUFA (mainly oleic acid, which accounts for around 20%), as well as the PUFA (n-6 and n-3 FA), which includes CLA, and phosphor- and sphingolipids from the milk fat globule [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major differences in the composition of milk and yogurts made from ewe’s and cow’s milk lie in the higher protein and fat content of the former, as well as higher amounts of vitamins, calcium, and phosphorus [15,65]. As indicated previously, ewe’s milk is richer in fat and SFA than cow’s milk, and a number of studies have shown that it offers a healthier nutritional profile than that of the cow, especially because of its higher content in short-chain FA (SCFA) from butyric to caproic acid, C4 to C10 (SCFA, see Table 2), associated with health benefits [66,67]. Besides SCFA, there are other beneficial lipids, such as the unsaturated FA, including MUFA (mainly oleic acid, which accounts for around 20%), as well as the PUFA (n-6 and n-3 FA), which includes CLA, and phosphor- and sphingolipids from the milk fat globule [68].…”
Section: Discussionmentioning
confidence: 99%
“…Besides SCFA, there are other beneficial lipids, such as the unsaturated FA, including MUFA (mainly oleic acid, which accounts for around 20%), as well as the PUFA (n-6 and n-3 FA), which includes CLA, and phosphor- and sphingolipids from the milk fat globule [68]. With respect to the fat content of dairy products, general dietary guidance to reduce total milk fat intake in order to decrease SFA consumption is currently considered inadequate, because that recommendation will also reduce the supply of bioactive lipid compounds and vitamins [67,69]. …”
Section: Discussionmentioning
confidence: 99%
“…It also contains a number of minor constituents that possess potential bioactivity beyond their pure nutritional significance [21, 22]. Milk fat is secreted as lipid droplets consisting of a hydrophobic triglyceride core enclosed within a thin membrane that is composed of a lipid and protein trilayer and is known as the milk fat/lipid globule membrane (MFGM) [22].…”
Section: Introductionmentioning
confidence: 99%
“…It also contains a number of minor constituents that possess potential bioactivity beyond their pure nutritional significance [21, 22]. Milk fat is secreted as lipid droplets consisting of a hydrophobic triglyceride core enclosed within a thin membrane that is composed of a lipid and protein trilayer and is known as the milk fat/lipid globule membrane (MFGM) [22]. The MFGM contains polar lipids including phospholipids (PLs) [phosphatidylserine (PS), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI)], sphingolipids [sphingomyelin (SM)] and gangliosides (GM3 and GD3) [2123].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation